Effect of Fluoxetine on Post-Hysterectomy Nursing of Patients with Endometrial Cancer: A Retrospective Study - Na Sun; Weijiao Yan; Linlin Wang; Jing Wang; Lin Wang (Clinical and Experimental Obstetrics & Gynecology)
Background: The incidence and mortality of endometrial cancer (EC) have increased in recent years. The incidence of psychological disorders induced by EC is also increasing. Fluoxetine is a prescribed antidepressant drug for managing mental illnesses. We retrospectively explored the effect of fluoxetine intervention on symptom checklist 90 (SCL-90), quality of life, Hamilton anxiety scale (HAMA), Hamilton depression scale (HAMD), and nursing satisfaction in patients with EC undergoing surgery. Methods: One hundred patients with EC undergoing hysterectomy were selected. Based on the different clinical nursing intervention methods, the patients were categorized into a control group (n = 50) and an intervention group (n = 50). Patients in the control group were provided routine care, including nutrition guidance, basic psychological nursing, pain care, rehabilitation exercise, and complication prevention, whereas patients in the intervention group were only treated with fluoxetine based on routine nursing protocols. The differences in SCL-90, quality of life, HAMA, HAMD scores, and nursing satisfaction between the two groups were observed. Results: No significant difference was observed in the SCL-90, quality of life score, HAMA, and HAMD between the two groups before treatment. After treatment, all items in the intervention group differed from those in the control group. The SCL-90 scores of the intervention group decreased after treatment, and all subscales of SCL-90 in the intervention group were reduced. All dimensions of quality of life were elevated in the control group after treatment. The HAMA and HAMD scores of patients in the intervention group declined considerably after treatment. Conclusions: Fluoxetine intervention effectively improved the quality of life of patients with EC undergoing hysterectomy, and ameliorated signs of anxiety and depression, thus promoting the recovery of the disease.